(3GdeOhfI aj Gdabg GdeGdcis - (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj,J (B191 (3g` s; (3QhGjI SMfhf Hf SYjO GdJfhMis
(3ChdgG (B:s
(3cJGH EQNGA GdSJhQ s
(3BNQgG (B:s
(3cJGH GdeCPhf dg ai GdJLGQI jMLQ Ydjg s
(3hQO GdYfhGf GdCUdi ai cX (B2 / 1644s
(3JHUQI GdYfhGf (B:s
(3QhGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B283 ; (3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B681s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdeGdcjs